ISOGRAMMA MEEK AND WORTHEN, 1870 (DICTYONELLIDA, BRACHIOPODA) FROM THE UPPER PALAEOZOIC OF EAST ASIA: IMPLICATIONS FOR BIOGEOGRAPHY AND EVOLUTIONARY TRENDS - Chen Z.Q.; Shi G.R. (My University, 2006)
Isogramma manchoukuoensis from the Upper Carboniferous of northeast China is redefined based on re-examination of the type specimens. Isogramma specimens from the Middle Permian of northeastern Japan are reassigned to I. aff. paotechowensis. A new family, Schizopleuroniidae, is proposed to include Schizopleuronia, but excludes Megapleuronia, which belongs to the Megapleuroniidae Liao, 1983. The family Isogrammidae is considered to be a transitional group in the eichwaldid-isogrammid-schizopleuronid evolutionary lineage within the Dictyonellida. A review of the global distribution of Isogramma species reveals that the genus has a total of 56 species ranging from the Mississippian (Early Carboniferous) to the Lopingian (Late Permian). Isogramma diversified rapidly after its origination in the middle Viséan and its species diversity remained high throughout the Mississippian. The genus possibly suffered a severe mid-Carboniferous boundary mass extinction, with no Early Carboniferous species surviving this event. Bashkirian Isogramma species show low diversity, followed by a global recovery in the Moscovian. During the latest Carboniferous Isogramma became highly diversified again. At the Carboniferous-Permian (C/P) transition Isogramma underwent another dramatic diversity drop, followed by several stepwise declines in diversity during the Early-Middle Permian. The Wuchiapingian I. sinosa is the last Isogramma species. Ukraine was the possible centre of origin for Isogramma. From Ukraine Isogramma spread over the Moscow Basin of Russia, Central Europe (Germany, Austria), South Europe (Spain) and West Europe (England, Ireland and Scotland), and migrated to the North American midcontinent and South China during the late Viséan (Early Carboniferous). In Europe, Isogramma migrated to Spain and eastern Europe (Serbia) in the Moscovian, from there it then dispersed into Central Asia (Uzbekistan and Kazakhstan) in the Kasimovian-Gzhelian. In the Palaeo-Tethys Isogramma migrated from South China to northeast and northwest China in the Moscovian, spread over the North China Block during the C/P transition, moved to Russian Siberia, Japan and the Qiangtang terrane of the Palaeo-Tethys during the Early-Late Permian. In North America Isogramma spread over the midcontinent during the Late Carboniferous and Early-Middle Permian and migrated to South America (Bolivia) in latest Carboniferous. Biogeographically, Isogramma was confined principally to the palaeo-tropical and warm to temperate zones throughout the Late Palaeozoic, with the possible exception of the Artinskian, as a questionable species of the genus also occurs in the Transbaikal region of southeast Russia. © 2005 Elsevier Ltd. All rights reserved.
Keywords: BRACHIOPODA; CARBONIFEROUS; EVOLUTION; ISOGRAMMA; MIGRATION; PERMIAN; Paleozoic::Carboniferous; Палеозой::Каменноугольная